Racial identity profiles among Black adolescents: impact on the relationship between daily racial microaggressions and health outcomes - Clifton, Richelle L.; Zapolski, Tamika C. B. (Frontiers in Adolescent Medicine, 2023)
Racial microaggressions are associated with multiple negative health outcomes, including increased distress, anxiety, and substance use. One factor that may impact this relationship and has received considerable attention in the literature is racial identity. Moreover, recent studies have employed the use of racial identity profiles to provide a more nuanced understanding of racial identity's impact on health outcomes. However, to date, few studies have explored the existence of racial identity profiles among adolescents or variability in risk pathways between racial microaggressions and health outcomes based on racial identity profiles among adolescents. For the current study, 48 Black adolescents (79.2% girls; Mage=17.13) completed measures of racial identity at baseline and daily diary measures of racial microaggressions, depression, anxiety, aggression, and substance use for 14 days. Four racial identity profiles were identified (labeled race-focused, undifferentiated, integrationist, and multiculturalist), with evidence to suggest reduced risk for aggression among youth within the race-focused profile but that these youth remain at risk for depression and cannabis use. The current study helps to inform the field of adolescent health, highlighting several areas for future research and intervention for mental and behavioral health outcomes among Black adolescents experiencing racial microaggressions.